A method of reactive control for 3D navigation of a nonholonomic robot in tunnel-like environments. (April 2020) - Matveev, Alexey S.; Magerkin, Valentin V.; Savkin, Andrey V.
Abstract: A nonholonomic under-actuated robot with a bounded control range travels inside an unknown and unstructured 3D tunnel bounded by a generic 2D surface. The robot has access to the nearest point of the surface and measures the distance to the surface along any ray from a narrow beam emitted from the robot around the direction to the nearest point. We present a new navigation law that ensures constant advancement of the robot through the tunnel, along with respecting a given safety margin to its surface, driving the robot to the desired distance to it, and subsequently maintaining this distance. This law is reactive: it generates the current control as a reflex-like reaction to the current observation. Rigorous justification of the proposed guidance approach is provided; its applicability and performance are confirmed by computer simulation tests.